2004
DOI: 10.1161/01.atv.0000109170.43400.2f
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Regulatory Factor-1 Mediates PPARγ-Induced Apoptosis in Vascular Smooth Muscle Cells

Abstract: Objective-Peroxisome proliferator-activated receptor ␥ (PPAR␥) possesses general beneficial effects on the cardiovascular system, such as inhibition of vascular lesion formation and atherosclerosis. However, molecular mechanisms for these effects are yet to be fully defined. The aim of this study is to elucidate whether interferon regulatory factor-1 (IRF-1), a transcriptional factor with anti-proliferative and pro-apoptotic properties, mediates PPAR␥-induced apoptosis in vascular smooth muscle cells (VSMCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 68 publications
3
23
0
Order By: Relevance
“…This effect is likely to be mediated through the PPAR␥ receptor, because apoptotic trigger in vascular smooth muscle cell cultures induced by thiazolidinediones has been related to PPAR␥ by previous reports by our group (Redondo et al, 2005) and other groups (BishopBailey et al, 2002). Other PPAR␥ agonists, such as troglitazone, also induced apoptosis in vascular smooth muscle cells (Gouni-Berthold et al, 2001;Lin et al, 2004) and in several tumor cell lines by a mechanism of action involving the decrease in the expression of the antiapoptotic protein Bcl-2 (Yoshizawa et al, 2002;Shiau et al, 2005). In this context, we also observed that PIO treatment decreased protein level of Bcl-2 in cells from both nondiabetic and diabetic patients analyzed by Western blotting.…”
Section: Discussionsupporting
confidence: 67%
“…This effect is likely to be mediated through the PPAR␥ receptor, because apoptotic trigger in vascular smooth muscle cell cultures induced by thiazolidinediones has been related to PPAR␥ by previous reports by our group (Redondo et al, 2005) and other groups (BishopBailey et al, 2002). Other PPAR␥ agonists, such as troglitazone, also induced apoptosis in vascular smooth muscle cells (Gouni-Berthold et al, 2001;Lin et al, 2004) and in several tumor cell lines by a mechanism of action involving the decrease in the expression of the antiapoptotic protein Bcl-2 (Yoshizawa et al, 2002;Shiau et al, 2005). In this context, we also observed that PIO treatment decreased protein level of Bcl-2 in cells from both nondiabetic and diabetic patients analyzed by Western blotting.…”
Section: Discussionsupporting
confidence: 67%
“…[75][76][77][78][79] The mechanisms include upregulation of growth arrest and DNA damageinducible gene 45 expression, 75,76 as well as p53 expression (Figure 2). 76 The transforming growth factor ␤1/Smad2 pathway 77,78 and IFN regulatory factor (IRF)-1 79 are also involved ( Figure 2). Pioglitazone increases transforming growth factor ␤1 secretion and phosphorylation of Smad2 in cultured VSMCs.…”
Section: Ppar-␥ Activation/inactivation In Vsmcsmentioning
confidence: 99%
“…77,78 PPAR-␥ agonists increase IRF-1 gene expression while inducing VSMC apoptosis, and conversely inhibition of IRF-1 by antisense oligonucleotide decreases the VSMC apoptosis in vitro. 79 However, VSMC apoptosis can decrease the stability of atherosclerotic plaques and predispose them to rupture. 80 Therefore, the inhibition on the VSMC apoptosis by PPAR-␥ agonists is a double-edged sword.…”
Section: Ppar-␥ Activation/inactivation In Vsmcsmentioning
confidence: 99%
“…Evidence exists that oral treatment with PPARg ligands may limit in-stent restenosis in human diabetics [92]. Interestingly, novel data suggest that TZDs impose their effect on SMCs via upregulation of IRF-1 and consecutive activation of p21 cip1 [93]. This particular pathway may also be responsible for the antimigratory effects of TZDs in human SMCs [94].…”
Section: Impact Of Interferon Regulatory Factor-1 (Irf-1) On Vascularmentioning
confidence: 99%